Construction of a BAC library and mapping BAC clones to the linkage map of Barramundi, Lates calcarifer - Lin Grace; Zhu Ze; Li Jian; Gong Ping; Feng Felicia; Lo Loong; Wang Chun; Yue Gen (BMC Genomics, 2008)
Abstract Background Barramundi (Lates calcarifer) is an important farmed marine food fish species. Its first generation linkage map has been applied to map QTL for growth traits. To identify genes located in QTL responsible for specific traits, genomic large insert libraries are of crucial importance. We reported herein a bacterial artificial chromosome (BAC) library and the mapping of BAC clones to the linkage map. Results This BAC library consisted of 49,152 clones with an average insert size of 98 kb, representing 6.9-fold haploid genome coverage. Screening the library with 24 microsatellites and 15 ESTs/genes demonstrated that the library had good genome coverage. In addition, 62 novel microsatellites each isolated from 62 BAC clones were mapped onto the first generation linkage map. A total of 86 BAC clones were anchored on the linkage map with at least one BAC clone on each linkage group. Conclusion We have constructed the first BAC library for L. calcarifer and mapped 86 BAC clones to the first generation linkage map. This BAC library and the improved linkage map with 302 DNA markers not only supply an indispensable tool to the integration of physical and linkage maps, the fine mapping of QTL and map based cloning genes located in QTL of commercial importance, but also contribute to comparative genomic studies and eventually whole genome sequencing.